2007
DOI: 10.1136/bmj.39238.890810.be
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial incentives on clinical autonomy and internal motivation in primary care: ethnographic study

Abstract: Objective To explore the impact of financial incentives for quality of care on practice organisation, clinical autonomy, and internal motivation of doctors and nurses working in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 16 publications
6
148
0
5
Order By: Relevance
“…143,144 Maintaining fee-for-service reimbursement supports provision of essential face-to-face services. However fee-for-service reimbursement should be broadened to embrace e-mail or Web-based virtual office visits, perhaps pegging them to some proportion of a routine office visit.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…143,144 Maintaining fee-for-service reimbursement supports provision of essential face-to-face services. However fee-for-service reimbursement should be broadened to embrace e-mail or Web-based virtual office visits, perhaps pegging them to some proportion of a routine office visit.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
“…Observation studies have confirmed that practices add staff, install electronic records, and network with community agencies to be eligible for incentives. 105,144 To be effective, criteria must be measurable, based on evidence, and amenable to medical management. Both the measures and incentives must be chosen and incentivized with care to assure providers do not simply deselect complex patients, for it is the complex patients who have the most to gain in a medical home environment.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
“…However, the fragmentation of roles in primary care reduces the possibility of dealing with human suffering in a multidimensional way. The QOF has the potential to reduce the doctors' role to that of achieving targets-completing computerised templates in the consultation and delegating more mechanical activities to nurses, seen by doctors as the best followers of guidelines 5 .…”
Section: Personal Continuity Of Carementioning
confidence: 99%
“…The QOF is a point-based system with three main types of indicators for obtaining the points 7 (Table 2). Moreover, QOF represents the biggest change in general practitioners contracts since 1966 8 and is considered the boldest such initiative in the world 5 . In 2004, each QOF point earned a practice about £75 sterling, evolving to £124.60 (2005/6) and reaching £130.00 (2011/12) 6 , representing a 20% increase in general practitioners' salaries 9 and costing the National Health Service (NHS) in excess of £1 billion 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation